PENGARUH FASILITAS KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA KANTOR BADAN KEPEGAWAIAN DAERAH PROVINSI MALUKU - Mery Watloly; Carla Tousalwa; Stevanus Johan Gomies (P3M Politeknik Negeri Ambon, 2025)
This study aims to analyze the effect of workplace facilities on employee work effectiveness at the Regional Personnel Agency of Maluku Province. Workplace facilities can influence employee work effectiveness. This research was conducted at the Regional Personnel Agency of Maluku Province to determine whether workplace facilities affect employee work effectiveness. This study uses a quantitative approach with a survey method, where data was obtained through questionnaires distributed to employees of the Regional Personnel Agency of Maluku Province. The sample taken in this study consisted of 44 employees. The method used in this research is a simple linear regression analysis method with the help of SPSS version 26 software, resulting in the regression equation Y = 25.305 + 0.195X. The hypothesis testing results show a t-count value of 2.113 with a probability of 1.68 or (p < 0.05). The test results indicate that the independent variable (workplace facilities) influences the dependent variable (employee work effectiveness) by 95%, while the remaining 5% is influenced by other variables. Based on these research findings, it can be concluded that workplace facilities have a positive and significant effect on employee work effectiveness at the Regional Personnel Agency of Maluku Province. Keywords : Work facilities; Work Effectiveness